President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2015)
The framework for professionalism in nursing began with Florence Nightingale. She set the bar rather high with the way she gave to others and her expectation of excellence in nursing practice. We, as perioperative nurses, are no different. We bear the tremendous responsibility of upholding the values of our profession and, as professionals, we are expected to demonstrate competent and skilful behaviors in alignment with our profession.